Low-profile conformal single-sided miniaturized frequency selective surface for wideband shielding - Malathi Kanagasabai; Lavanya Viswanathan; M. Gulam Nabi Alsath; Sandeep Kumar Palaniswamy; Sachin Kumar; Santhya Premdharshini Premkumar; Hyun Chul Choi; Kang Wook Kim (Scientific Reports)
Abstract This paper presents an ultra-wideband (UWB) frequency selective surface (FSS) that is conformal, low-profile, single-layered, and miniaturized. The designed simple modified star swastika (MSS) arms offer a wide bandwidth of 7.5 GHz with transmission nulls ranging from 3.1 to 10.6 GHz. The 0.0008λ 0 thin MSS FSS unit cells form a periodic pattern with a physical form factor of 0.041λ 0 and 61% miniaturization. The proposed FSS has a -10 dB fractional bandwidth of 109.48% and a peak shielding of 67.9 dB at 7.1 GHz. The designed FSS has a figure of merit (FoM) of 10.25 (λ 0/U), where U represents the unit cell size of the FSS. In both transverse electric (TE) and transverse magnetic (TM) modes, incoming waves can be stable with incidence angles (θ) up to 75º and less than 1% frequency deviation. To gain a physical understanding of the FSS unit cell, an equivalent circuit model (ECM) analysis is conducted. The FSS prototype has been built, and the measured results are validated with simulated results. Hence, the proposed MSS FSS could be a promising solution for wideband shielding.